Never Again? - Tchaicovsky, Melitta (United States : ArtNetwork Productions, 2009)
A close-up on the humanitarian crisis in Sudan, this film tries to decipher the civil war and its aftermath through interviews with survivors in displacement camps in Sudan and Chad as well as refugees, and activists in Europe and in Israel. It also attempts to understand the reason for the ongoing plight of the Sudanese people as well as the international community’s inability to assist.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films